Fabrication, optimization, and in vitro evaluation of docetaxel-loaded nanostructured lipid carriers for improved anticancer activity. (2nd April 2020) - Mathur, Prateek; Sharma, Swati; Rawal, Shruti; Patel, Bhoomika; Patel, Mayur M.
Abstract: Lung cancer is the leading cause of cancer-related deaths in both men and women worldwide. It is the leading cancer killer in both men and women in every Ethnic Group. A major problem associated with chemotherapies against their lung cancer is the lack of selective toxicity, which results in a narrow therapeutic index thereby compromising clinical prognosis. To circumvent these challenges, the present investigation sought to develop a docetaxel-loaded nanostructured lipid carrier system (DTX-NLCS) for the treatment of lung cancer. A 3-factor/3-level Box-Behnken Design was applied to systematically optimize the DTX-NLCS parameters. The amount of drug, emulsifier concentration, and homogenization speed was selected as independent variables, while the particle size and % entrapment efficiency (%EE) were selected as dependent variables. The optimized batch parameters were 29.81 mg drug, 19.97% w/w emulsifier, and 13 200 (rpm) speed of homogenization with a mean particle size of 154.1 ± 3.13 nm and a mean %EE of 86.12 ± 3.48%. The in vitro lipolysis experiments revealed that the optimized DTX-NLCs were stabilized by 10% w/w PEG 4000 mono-stearate and exhibited an anti-lipolytic effect. Furthermore, the in vitro gastrointestinal stability studies (at pH-1.2, pH-4.5, pH-6.8, and pH-7.4) revealed that the optimized developed system could withstand various GI tract media. The in vitro dissolution studies depicted a pH-independent controlled-release consistent with the Weibull model. In vitro cytotoxicity studies using NCI-H460 cell lines further revealed that there was a reduction in IC50 values in the DTX-NLCS treated cells as compared to those treated with the pure drug, indicating an improved efficiency for the developed system. Graphical Abstract: